2018
DOI: 10.1002/adsc.201800591
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Transfer Complex Promoted Regiospecific C−N Bond Cleavage of Vicinal Tertiary Diamines

Abstract: A catalyst-free, charge-transfer complex promoted coupling of sulfonyl chlorides with vicinal tertiary diamines to generate sulfonamides is presented. Mechanistic studies showed that these reactions are proceeded via charge transfer of vicinal tertiary diamines to sulfonyl chlorides, forming the unstable sulfonyl quaternary ammonium like complexes which induced the regiospecific intramolecular CÀN bond cleavage of vicinal tertiary diamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The activation and transformation of CÀ N bond in aliphatic cyclic amines has become a useful pathway for the construction of new CÀ N/CÀ X bonds. [136] Recently, Fu et al reported a visible light-induced ring opening of N-alkyl-4-piperidinols for the synthesis of (E)-homoallylamines with high region-and stereoselectivities (Scheme 42). [137] The transformation was promoted by charge-transfer complex (CT complex) using metal-free alizarin yellow R (AYR) as the organocatalyst under mile conditions.…”
Section: Photoinduced Radical-radical Cross-coupling Reactions Promotmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation and transformation of CÀ N bond in aliphatic cyclic amines has become a useful pathway for the construction of new CÀ N/CÀ X bonds. [136] Recently, Fu et al reported a visible light-induced ring opening of N-alkyl-4-piperidinols for the synthesis of (E)-homoallylamines with high region-and stereoselectivities (Scheme 42). [137] The transformation was promoted by charge-transfer complex (CT complex) using metal-free alizarin yellow R (AYR) as the organocatalyst under mile conditions.…”
Section: Photoinduced Radical-radical Cross-coupling Reactions Promotmentioning
confidence: 99%
“…The activation and transformation of C−N bond in aliphatic cyclic amines has become a useful pathway for the construction of new C−N/C−X bonds [136] . Recently, Fu et al.…”
Section: Photoinduced Radical‐radical Cross‐coupling Reactions Promot...mentioning
confidence: 99%
“…Indeed, the diamines worked as N-donor ligands and chiral auxiliaries with many of metal ions such as Ca [7], Fe [8], Ag [9], Ni [10], Pd [11], and Rh [12], indeed, it explored in various catalyzed protocols and were successively employed as efficient catalysts for many transformations in organic synthesis. In this aspect, the aminals (gem-diamines) have been considered as promising electrophiles in metal-catalyzed nucleophilic addition reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…[3] The CÀ N bond cleavage reaction of 1,2,3,4-tetrahydroisoquinolines and N,N'diarylimidazolines with tert-butylnitrite under O 2 atmosphere was developed to generate the corresponding N-nitrosoaminocarbonyl compounds (Scheme 1C). [4] Recently, a photoredox-catalyzed CÀ N bond cleavage of cyclic amines bearing a urea group, which features the hydrogen bonding interaction with nucleophiles (Scheme 1D(a)) [5] and charge-transfer promoted CÀ N bond cleavage of trialkyl amines with sulfonyl chlorides (Scheme 1D(b)) [6] have been reported. On the other hand, we were able to achieve several oxidative transformations via umpolung of bromide reactivity, including bromocyclization, [7] direct CÀ H oxidation, [8] and dual functionalization.…”
mentioning
confidence: 99%